KEHIJAUAN DAUN, KADAR KHLOROFIL, DAN LAJU FOTOSINTESIS VARIETAS LOKAL DAN VARIETAS UNGGUL PADI SAWAH YANG DIBUDIDAYAKAN SECARA ORGANIK KAITANNYA TERHADAP HASIL DAN KOMPONEN HASIL - Achmad Fatchul Aziez; Didik Indradewa; Prapto Yudhono; Eko Hanudin (JURNAL ILMIAH AGRINECA, 2014)
Superior varieties and local varieties of paddy fields have different physiological characters so when cultivated organically made possible the result would have been different. The purpose of this research is to know the relation between greenish of leaf, chlorophyll content and rate of photosynthesis as well as local and superior varieties on the yield and yield component. This research was carried out in the greenhouse of Agriculture Faculty, Gadjah Mada University Banguntapan Sleman, in October 2012 to February 2013. The experimental design was Completely Randomized Design (CRD) factorial, 2 factors of treatment and repeated 3 times. Factor I was kind of cultivation, namely organic cultivation and conventional cultivation. Factor II is a kind of rice varieties of rice field consists of 5 kinds of paddy rice varieties consisting of local varieties (mentikwangi, pandanwangi and cianjur) and superior varieties (IR64 and cisedane). The observed parameter includes the greennish of leaf 6, 8, and 10 weeks after planting (WAP), chlorophyll a, chlorophyll b, total chlorophyll, photosynthetic rate and yield and yield components. The results of this research show that the greennish leaf, level of chlorophyll a, chlorophyll b and total chlorophyll as well as the photosynthetic rate of rice fields cultivated organically lower than conventional cultivation. Number of total grain, grain percentage content and grain yield in organic cultivation are lower than conventional farming, but the weight of 1000 grains increased. Mentikwangi variety in organic cultivation the result is increased.